Raw Multi-Channel Seismic Shot Data from the Aleutian Islands and Bering Sea Shelf acquired during R/V Maurice Ewing expedition EW9409 (1994) (IEDA: Marine-Geo Digital Library, 2006)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9409 conducted in 1994 (Chief Scientist: Dr. Susan McGeary; Investigator: Dr. John Diebold). These data files are of SEGY format and include Multi-Channel Reflection Seismic shot data that have not been processed. Data were acquired as part of the projects: Pacific to Bering Shelf Deep Seismic Reflection Experiment, Aleutian Arc Seismic Experiment, and Seismic Velocity Structure of the Aleutian Arc and Bering Shelf and the Composition of Continental Growth, and funding was provided by NSF grants: EAR92-04998, OCE94-01374, OCE94-11541, OCE94-12683, and OCE94-12684. These data are cited by Holbrook et al., 1999, Lizarralde et al., 2002, Walker et al., 2003, Shillington et al., 2004, and Van Avendonk et al., 2004.